(3MGTjI Ydi CfhGQ GdJfRjd hCSQGQ GdJChjds - (3TjNj RGOg, YHO GdQMef Hf eMeO SdjeGf, J (B1078 (3g`s ((3YHO GddWja GdHgGFj GdMfajs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj fhQ bdhH GdYdeGA HCfhGQ GdJfRjd Ke Efj GNJQJ ef Jdc GdcJH GdcJGH GdehShe HGfhGQ GdJfRjd hCSQGQ GdJChjd GdPj Ufag Yde GdgOi GdeYQha HGdbGVj GdHjVGhj adPdc CdReJ Ydi faSj Cf CMQQ eG XaQJ Hg ef GdahGFO s
(3BNQgG (B:s
(3bhdg (B: (3aj bhdg JYGdi hEPG bJdJe faSG (B- (3Edi bhdg JYGdi (B: (3Ke bSJ bdhHce hgj CbQH Edjg ef Gdbhe hVeGFQge GdeJbOeI hdjS dg Cf jMedgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 332s
(3eYLe GdeDdajf (B2 / 111s
(3gOjI GdYGQajf (B1 / 549s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJaSjQ hYdhe GdbQBfs